2020
DOI: 10.1177/2632352420975043
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of childhood bereavement in Scotland and its relationship with disadvantage: the significance of a public health approach to death, dying and bereavement

Abstract: Background and Method: There is an absence of research on the prevalence of bereavement during early childhood and the relationship between childhood bereavement and socioeconomic status (SES) and this poses a challenge in both understanding and supporting children’s bereavement experiences. Using longitudinal data from the Growing Up in Scotland study, which tracks the lives of three nationally representative cohorts of children, this paper aimed to address these gaps in research. It specifically drew on data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…However, these were synthesized in the narrative review. Where possible, within-group effect sizes (Cohen's d) were extracted from the papers; if unavailable, they were calculated using the available statistics (e.g., pre/post means and SDs) 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these were synthesized in the narrative review. Where possible, within-group effect sizes (Cohen's d) were extracted from the papers; if unavailable, they were calculated using the available statistics (e.g., pre/post means and SDs) 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Standard errors for these effect sizes were calculated using the N of the intervention group only, to be consistent with the within-groups effect sizes from the other studies 2. As few studies reported pre and post-test correlations between outcomes, r = 0.5 was substituted in for the calculation of the standard error for each effect size.…”
mentioning
confidence: 97%
“…Høeg et al (2019) did not find that socioeconomic status or psychiatric illness in the family had an influence on the significantly lower attainment rates among bereaved children. However, a Scottish cohort study (Paul & Vaswani, 2020) including 2,815 children found that children born into the lowest income households had a greater risk of losing a parent or sibling than children born into high-income households. Berg et al (2014) found bereaved children to be at increased risk of lower grades and school failure but were able to attribute such difficulties to preexisting socio-economic disadvantages and psychosocial problems in the family.…”
Section: Risk and Protective Factorsmentioning
confidence: 99%
“…Children from poor families are at higher risk of experiencing bereavement (Paul & Vaswani, 2020), with parental death between two and five times more common among low versus high socioeconomic households and twice as common among adolescents of racial minority backgrounds (Feigelman et al, 2017). Thyden et al (2020) found that whilst 4.2% of white youth had experienced a death in the family, in contrast, 8.3% of Blacks, 9.1% of Asians and 13.8% of Native Americans had experienced family bereavement.…”
Section: Disadvantaged Youthmentioning
confidence: 99%